Framing Corporate Social Responsibility On the Websites Of Company (Mudflow Incident) - Utama, A.A Gde Satia (Archives of Business Research, 2017)
The research conduct through the official website of the company whichis engaged in energy and oil gas drilling (mudflow incident). The purpose of this research to frame of the company from their official website to reveal the CSR program, especially incorporate governance, environmental, and social. The research focus on three main areas : corporate governance and reporting, environmental policy, and social policy. Measurement of the quantity of information presented using the indexas an indicator of Publicity. Data will analyzed, with frame analysis. The data obtained and processed using qualitative software called Nvivo11. The results of this research will inform Publicity of CSR by the company that involved mudflow incident.